Glutamine starvation inhibits snakehead vesiculovirus replication via inducing autophagy associated with the disturbance of endogenous glutathione pool. Issue 86 (March 2019) - Li, Cheng; Sun, Lindan; Lin, Hanzuo; Qin, Zhendong; Tu, Jiagang; Li, Jun; Chen, Keping; Babu V, Sarath; Lin, Li
Abstract: Autophagy is a degradation cellular process which also plays an important role in virus infection. Glutamine is an essential substrate for the synthesis of glutathione which is the most abundant thiol-containing compound within the cells and plays a key role in the antioxidant defense and intracellular signaling. There is an endogenous cellular glutathione pool which consists of two forms of glutathione, i.e. the reduced form (GSH) and the oxidized form (GSSG). GSH serves as an intracellular antioxidant to maintain cellular redox homeostasis by scavenging free radicals and other reactive oxygen species (ROS) which can lead to autophagy. Under physiological conditions, the concentration of GSSG is only about 1% of total glutathione, while stress condition can result in a transient increase of GSSG. In our previous report, we showed that the replication of snakehead fish vesiculovirus (SHVV) was significant inhibited in SSN-1 cells cultured in the glutamine-starvation medium, however the underlying mechanism remains enigmatic. Here, we revealed that the addition of L-Buthionine-sulfoximine (BSO), a specific inhibitor of the GSH synthesis, could decrease the γ- glutamate-cysteine ligase (GCL) activity and GSH levels, resulting in autophagy and significantly inhibition of the replication of SHVV in SSN-1 cells cultured in the complete medium. On the other hand, the replication of SHVV was rescued and the autophagy was inhibited in the SSN-1 cells cultured in the glutamine-starvation medium supplemented with additional GSH. Furthermore, the inhibition of the synthesis of GSH had not significantly affected the generation of reactive oxygen species (ROS). However, it significantly decreased level of GSH and enhanced the level of GSSG, resulting in the decrease of the value of GSH/GSSG, indicating that it promoted the cellular oxidative stress. Overall, the present study demonstrated that glutamine starvation impaired the replication of SHVV in SSN-1 cells via inducing autophagy associated with the disturbance of the endogenous glutathione pool. Highlights: Glutamine starvation induced autophagy in SSN-1 cells. Inhibition of the synthesis of glutathione induced autophagy, resulting in the inhibiting of SHVV replication. Glutamine starvation induced autophagy by disturbing endogenous glutathione pool as well as GSH/GSSG ratio.